2015
DOI: 10.1038/srep10217
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid-membrane migration method to isolate high-purity adipose-derived stem cells from fat tissues

Abstract: Human adipose-derived stem cells (hADSCs) exhibit heterogeneous characteristics, indicating various genotypes and differentiation abilities. The isolated hADSCs can possess different purity levels and divergent properties depending on the purification methods used. We developed a hybrid-membrane migration method that purifies hADSCs from a fat tissue solution with extremely high purity and pluripotency. A primary fat-tissue solution was permeated through the porous membranes with a pore size from 8 to 25 μm, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Typically, higher expression of MSC surface markers on hADSCs is found with increasing passage number14171819. However, we found that expression of some pluripotent genes such as Oct3/4, Nanog , and Klf4 , which were typical genes used for the transduction of somatic cells in reprogramming into hiPSCs1234, decreased after culture of cells in SVF solution on TCPS in our previous study16, whereas the pluripotent gene expression of the cells in SVF solution could be maintained after purification by filtration via porous membranes16. These surprising results indicate that hADSC characteristics depend on the method used for isolation of hADSCs from SVF solution.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Typically, higher expression of MSC surface markers on hADSCs is found with increasing passage number14171819. However, we found that expression of some pluripotent genes such as Oct3/4, Nanog , and Klf4 , which were typical genes used for the transduction of somatic cells in reprogramming into hiPSCs1234, decreased after culture of cells in SVF solution on TCPS in our previous study16, whereas the pluripotent gene expression of the cells in SVF solution could be maintained after purification by filtration via porous membranes16. These surprising results indicate that hADSC characteristics depend on the method used for isolation of hADSCs from SVF solution.…”
mentioning
confidence: 60%
“…1a). Mesenchymal stem cell (MSC) marker expression typically increases after SVF solution is cultured on conventional tissue culture polystyrene (TCPS) dishes141516. MSC surface markers in SVF solution often show less than 10–20% expression, whereas MSC surface markers of the cells after culture on TCPS (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore it was represented that cells obtained from human liposuction fat have special ability to divide into other cell types. These MSCs were called adipose-drived stem cells (ASCs) 55 . ASCs are abundant and can be harvested with minimal invasive procedure.…”
Section: Stem Cells and Tissue Engineeringmentioning
confidence: 99%
“…HSCs derived from bone marrow (that can generate all types of different blood cells) 137 , and different types of MSCs found in other tissues such as skeletal, bone marrow are some examples of this subject. Adipose derived SCs (ADSCs) are multipotent MSCs that exist in subcutaneous fat deposits and are easily isolated from material obtained using lipoplasty (fat removal) 55 .…”
Section: Stem Cells In Microfluidic-based Neural Tissue Engineeringmentioning
confidence: 99%